(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
The aim of this study was to investigate the relationship between transformational leadership role and organizational health in the General Directorate of Education of North Khorasan. Their validity was confirmed and their reliability was obtained using Cronbach’s test of 88% and 78%, respectively. The study population is 153 employees of the General Directorate of Education of North Khorasan who were active in 2021. The statistical sample includes 110 employees; which were selected by random sampling method. Findings showed that there is a significant relationship between the components of research (the role of transformational leader with desirable influence, the role of transformational leader with inspirational motivation, the role of transformational leader with mental motivation) and organizational health. As a result, in order to make the organization healthier and achieve this important goal, managers should make efforts to improve their leadership role in order to solve organizational problems by establishing a committed relationship along with a contingent approach to environmental variables.